EXPLORATION OF CHITINOLYTIC MICROORGANISMS FROM SEAWATER AS ANTI-CANDIDIASIS AGENTS USING FUNCTIONALIZED CHITIN SUBSTRATE DERIVED FROM GREEN MUSSEL WASTE - Adnyanaschah, Rahadhyan; Ismail, Dzava Prawinsyah Fairus; Mahardika, Bintang Satrio; Putri, Yolla Adellia; Shafa, Nafis; Rostinawati, Tina (Jurnal Ilmiah Farmako Bahari, 2025)
Candidiasis is a Candida sp. infection (Candida albicans in common) that happens in nails, hairs, skin, and oesophagus, with around 20-25% prevalence in Indonesia. Chitin is one of the main components of its cell wall and serves as a target for candidiasis therapy using natural degradant compounds, such as chitinase enzyme. Chitinase enzyme is collected from chitinolytic bacteria found massively in chitin-rich environments like seawater. The screening is needed to identify the varieties of bacteria with chitinolytic activity. The screening was done using green mussel waste (Perna viridis), which contains 14-35% chitin and reached 10.776,75 tons of trash in 2020. This research aims to get a chitinolytic bacteria using green mussels as a chitin substrate source and a chitinolytic bacteria with anti-candidiasis activity. This research was conducted by isolating chitin from green mussel shells, chitinolytic bacteria screening, and anti-candidiasis activity test. Results collected from 5.00, 5.08, and 5.18 km isolates were the Vibrio alginolyticus, Vibrio neocaledonicus, and Marinobacter persicus species, which had a chitinolytic index of 1.246, 1.560, 1.492 also 64.29; 61.30; 69.01 U/ml chitinase enzymatic activity. The highest anti-candidiasis activity was found in a sample 5,18 km from the coast of Kejawanan Beach based on the number of chitinase enzyme activity and the chitinolytic index.